Unicameral bone cyst of the lunate in an adult: case report - Gündeş, Hakan (BioMed Central, 2010)
We report a case of a symptomatic unicameral (simple) bone cyst of the lunate in a 42-year- old woman. The lesion was treated with curettage and cancellous autogenous iliac bone grafting. At five years of follow-up the wrist was pain free, there were no limitations of motion, and the radiographs showed complete obliteration of the cavity. To the best of our knowledge, no other unicameral bone cyst of the lunate has been reported in an adult. Cysts with significant cavities at the carpal bones in an adult should be approached cautiously, as they may require early curettage and bone grafting for healing, before collapse and degenerative changes occur.